Controllable synthesized CoP-MP (M=Fe, Mn) as efficient and stable electrocatalyst for hydrogen evolution reaction at all pH values. (26th July 2019) - Du, Yunmei; Wang, Zuochao; Li, Hongdong; Han, Yi; Liu, Yanru; Yang, Yu; Liu, Yongjun; Wang, Lei
Abstract: The introduction of metal atom or heteroatom into transition metal phosphide is an effective strategy to enhance the electrochemical activity for hydrogen evolution reaction, while the controllable synthesis and purposeful design of efficient and stable transition metal phosphide based electrocatalyst with typical structural morphology is still a big challenge. Here, we investigated the relationship among the variety of the doped metal element (Fe and Mn), the corresponding morphology and electrocatalytic performance of the obtained sample for hydrogen evolution reaction. We found that with the doping of Fe and Mn, the cylinder-like CoP has transformed into microflower-like CoP-FeP and rambutan-like CoP-MnP, respectively. Meanwhile, the obtained CoP-FeP exhibits the excellent electrocatalytic activity hydrogen evolution reaction (HER) over a wide pH range (0–14), followed by CoP-MnP and CoP, resulting from the typical nanostructure and the moderately optimized electronic structure of P and Co center. Graphical abstract: Image 1 Highlights: CoP-MP (M = Fe, Mn) nanomaterials with different morphology have been controlled synthesized. CoP-FeP shows excellent electrochemical performance for HER over a wide pH range (0–14). The introduction of Fe or Mn element could optimized electronic structure of Co centers and P.